Pengembangan Model Pendidikan Berbasis Integrasi Ilmu Dan Islam Di Universitas Islam Riau - Yenni Yunita; Karim, Nazir; Alpizar, Alpizar (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2025)
Abstract Riau Islamic University was established in 1962 with the main objective of integrating Islamic values ​​in the implementation of higher education. Since its inception, UIR has been committed to eliminating the dichotomy between general knowledge and religious knowledge, as well as overcoming the secularization of knowledge. This study aims to develop an educational model based on the integration of knowledge and Islam at Riau Islamic University. This type of research is research and development (Research and Development) or R & D which uses the ADDIE model. The results of this study are First, the concept of integrating Islam and knowledge has existed since the establishment of this campus. Several educational values ​​that can be integrated into knowledge are spread across various courses, including: (1) Morals, described as 6 values: Sincerity, Honesty, Trustworthiness, Kindness, Togetherness, and Justice. (2) Knowledge, described as 2 values: Intelligence and Hard work. (3) Charity, described as the value of preaching. Second, the Education Model based on